2013
DOI: 10.1016/j.ydbio.2012.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Abelson interactor-1 (ABI-1) interacts with MRL adaptor protein MIG-10 and is required in guided cell migrations and process outgrowth in C. elegans

Abstract: Directed cell migration and process outgrowth are vital to proper development of many metazoan tissues. These processes are dependent on reorganization of the actin cytoskeleton in response to external guidance cues. During development of the nervous system, the MIG-10/RIAM/Lamellipodin (MRL) signaling proteins are thought to transmit positional information from surface guidance cues to the actin polymerization machinery, and thus to promote polarized outgrowth of axons. In C. elegans, mutations in the MRL fam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 67 publications
2
18
0
Order By: Relevance
“…By contrast, MIG-10 did not bind to GST alone. Two concurrent studies have also found that MIG-10 can bind to full length ABI-1, using yeast 2 hybrid and also co-immunoprecipitation [28], [29]. Together, these observations identify ABI-1 as a potential member of the MIG-10 outgrowth-promoting complex.…”
Section: Resultsmentioning
confidence: 72%
See 1 more Smart Citation
“…By contrast, MIG-10 did not bind to GST alone. Two concurrent studies have also found that MIG-10 can bind to full length ABI-1, using yeast 2 hybrid and also co-immunoprecipitation [28], [29]. Together, these observations identify ABI-1 as a potential member of the MIG-10 outgrowth-promoting complex.…”
Section: Resultsmentioning
confidence: 72%
“…This interaction could help to explain how actin polymerization is spatially regulated during guidance, since MIG-10 is asymmetrically localized in response to guidance cues [15], [18]. Concurrent work has indicated that the interaction between MIG-10 and ABI-1 can also regulate excretory canal morphogenesis and synapse formation [28], [29], Moreover, recent work has also shown that axon guidance cues and receptors are involved in regulating the WVE-1 complex during embryonic morphogenesis [33]. Together, these observations suggest that the interactions between axon guidance signaling components and the WVE-1 actin regulatory complex may be important in multiple aspects of actin-dependant developmental processes.…”
Section: Discussionmentioning
confidence: 96%
“…Although MIG-10 (Lamellipodin) regulates diverse biological processes [12,13,14], mig-10 ’s function and regulation in cell invasive behavior are not fully understood. Using AC invasion in C .…”
Section: Discussionmentioning
confidence: 99%
“…MIG-10 regulates axon guidance, neuronal migration [12], the clustering of vesicles at the synapse [13], and the outgrowth of the processes of the excretory cell [14]. In AC invasion, we have previously found that mig-10 functions largely outside of unc-6 (netrin) signaling [15] in contrast to mig-10 acting downstream of unc-6 in axon guidance [12].…”
Section: Introductionmentioning
confidence: 99%
“…When UNC-6 is absent, the ability of UNC-40-mediated outgrowth activity to polarize is suppressed by UNC-53/Nav2 activity (Kulkarni et al 2013). UNC-53 is a scaffold protein that interacts with ABI-1-a member of the WAVE complex that regulates the Arp2/3 complex-and ABL-1 is known to interact with MIG-10 ( Schmidt et al 2009;Stringham and Schmidt 2009;McShea et al 2013). UNC-53 may also be tied to the Wnt response.…”
Section: Models Of Axon Guidancementioning
confidence: 99%